The relaxant effect of Ferula assafoetida on smooth muscles and the possible mechanisms - Khazdair Mohammad Reza; Boskabady Mohammad Hossein (Shahrekord University of Medical Sciences, 2015)
Asafoetida (Ferula asafoetida) an oleo-gum-resin belongs to the Apiaceae family which obtained from the living underground rhizome or tap roots of the plant. F. assa-foetida is used in traditional medicine for the treatment of variety of disorders. Asafoetida is used as a culinary spice and in folk medicine has been used to treat several diseases, including intestinal parasites, weak digestion, gastrointestinal disorders, asthma and influenza. A wide range of chemical compounds including sugars, sesquiterpene coumarins and polysulfides have been isolated from this plant. This oleo-gum-resin is known to possess antifungal, anti-diabetic, anti-inflammatory, anti-mutagenic and antiviral activities. Several studies investigated the effects of F. asafoetida gum extract on the contractile responses induced by acetylcholine, methacholin, histamine and KCl on different smooth muscles. The present review summarizes the information regarding the relaxant effect of asafetida and its extracts on different smooth muscles and the possible mechanisms of this effect.